Infant sleep and child mental health: a longitudinal investigation. Issue 7 (9th March 2020) - Cook, Fallon; Conway, Laura J; Giallo, Rebecca; Gartland, Deirdre; Sciberras, Emma; Brown, Stephanie
Abstract : Objective: To determine whether infants with severe persistent sleep problems are at increased risk of (1) meeting diagnostic criteria for a psychiatric disorder (age 10 years), and (2) having elevated symptoms of mental health difficulties (ages 4 and 10 years), in comparison with infants with settled sleep. Design and setting: Prospective longitudinal community cohort study—the Maternal Health Study. Mothers completed questionnaires/interviews at 15 weeks' gestation; 3, 6, 9 and 12 months post partum; and when their child turned 4 and 10 years old. Measures included parental report of infant night waking and sleep problems and child mental health (Strengths and Difficulties Questionnaire; Spence Children's Anxiety Scale; Development and Well-being Assessment). Participants: 1460 mother-infant dyads. Results: 283 (19.4%) infants had persistent severe sleep problems, 817 (56.0%) had moderate/fluctuating sleep problems and 360 (24.7%) infants were settled. Infants with persistent severe sleep problems were more likely to report emotional symptoms at age 4 (adjusted odds ratio (AOR)=2.70, 95% CI 1.21 to 6.05, p=0.02), and meet diagnostic criteria for an emotional disorder at age 10 (AOR=2.37, 95% CI 1.05 to 5.36, p=0.04). Infants with persistent severe sleep problems also had elevated symptoms of separation anxiety (AOR=2.44, 95% CI 1.35 to 4.41, p<0.01), fear of physical injury (AOR=2.14, 95% CI 1.09 to 4.18, p=0.03) and overall elevated anxiety (AOR=2.20, 95% CI 1.13 to 4.29, p=0.02) at age 10. Conclusions: Infants with persistent severe sleep problems during the first postnatal year have an increased risk of anxiety problems and emotional disorders at age 10.